2018
DOI: 10.4082/kjfm.17.0060
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Family Mealtime and Depression in Elderly Koreans

Abstract: BackgroundSeveral studies have revealed the frequency of family mealtimes to be inversely associated with depressive symptoms in adolescents. However, there have been few studies in older populations. This cross-sectional study investigated the association between family mealtime frequency and depressive symptoms in elderly Koreans.MethodsThis study analyzed 4,959 elderly men and women (aged 65 years or older) who participated in the Korea National Health and Nutrition Examination Survey. Self-administered que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
2
16
1
1
Order By: Relevance
“…Increased pressure in the academic, marriage, and employment realms has forced young adults to delay getting married and live alone for a longer period, which causes them to have individualistic values and decreases their social exchanges with others [37]. This study also demonstrated that lower socioeconomic levels [24,35,38,39], including lower income levels and education attainment, and poorer physical health, such as the present of a chronic disease [40] or smoking [14], have a higher association between eating alone and depression and suicidal ideation.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Increased pressure in the academic, marriage, and employment realms has forced young adults to delay getting married and live alone for a longer period, which causes them to have individualistic values and decreases their social exchanges with others [37]. This study also demonstrated that lower socioeconomic levels [24,35,38,39], including lower income levels and education attainment, and poorer physical health, such as the present of a chronic disease [40] or smoking [14], have a higher association between eating alone and depression and suicidal ideation.…”
Section: Discussionmentioning
confidence: 73%
“…Chronic illness, smoking status, and drinking status were also included. Covariates were re-categorized based on previous research [12,14,20,24,26] . Non-drinker group was analyzed as a reference, due to the nature of the questionnaires, to distinguish among non-drinker, drink less than once a month and drink once a month based on our previous study [27].…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…This study evaluated nutrient intake and dietary quality of people who eat alone and investigated the differences in those factors by gender and age. It has been shown that older adults and one-person households tend to eat alone [ 5 6 ], and the rate of eating alone in women is about twice that of men [ 5 ]. The same demographic characteristics of solo eaters were observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The number of one-person households increased from 2.22 million (15.5% of the Korean population) in 2000 to 5.62 million (28.6% of the population) in 2017 [ 4 ]. One of 4 elderly Koreans aged 65 years old or above were reported to have eaten alone during the last year [ 5 ]; moreover, one-person households were more likely than multi-person households to eat alone [ 6 7 ]. Consequently, the number of ‘solo eaters’ is expected to increase in concert with the demographic changes.…”
Section: Introductionmentioning
confidence: 99%